Harnessing the power of professional associations to unite the third-space community - Craig Morley; Nicola Grayson (Journal of Learning Development in Higher Education)
In this opinion piece, we discuss career pathways and trajectories for third space professionals. We explore the unique difficulties of career progression for those in the third space compared to the more recognised and established routes for academic colleagues, or those who work in professional services who are employed on ‘academic’ contracts. We argue that, in order to overcome these difficulties and make potential career pathways and trajectories more visible, we should conceptualise the third space itself as a collective unity. In creating an interconnected third space community, individuals could be supported to move between and across territories and boundaries which encompass different professional identities within the wider third space itself as a professional sphere. In support of this, we issue a ‘Call for Collaboration’ to our respective third space professional associations. We argue, that by enhancing and increasing interaction between fields within the third space, opportunities can be cross-promoted more effectively, resulting in greater career development opportunities and increased support for respective members.